Reconceptualising authenticity for English as a global language - Pinner, Richard S. (Second language acquisition, 2016)
This book explores authenticity as it relates to second language acquisition with a focus on the instruction of English as a foreign language. It discusses the theoretical issues surrounding authenticity and presents it as a complex dynamic construct that can only be understood by examining it from social, individual and contextual dimensions.